The Emerging Roles of Axonemal Glutamylation in Regulation of Cilia Architecture and Functions - Yang, Wen-Ting; Hong, Shi-Rong; He, Kai; Ling, Kun; Shaiv, Kritika; Hu, JingHua; Lin, Yu-Chun (Frontiers in Cell and Developmental Biology, 2021)
Cilia, which either generate coordinated motion or sense environmental cues and transmit corresponding signals to the cell body, are highly conserved hair-like structures that protrude from the cell surface among diverse species. Disruption of ciliary functions leads to numerous human disorders, collectively referred to as ciliopathies. Cilia are mechanically supported by axonemes, which are composed of microtubule doublets. It has been recognized for several decades that tubulins in axonemes undergo glutamylation, a post-translational polymodification, that conjugates glutamic acid chains onto the C-terminal tail of tubulins. However, the physiological roles of axonemal glutamylation were not uncovered until recently. This review will focus on how cells modulate glutamylation on ciliary axonemes and how axonemal glutamylation regulates cilia architecture and functions, as well as its physiological importance in human health. We will also discuss the conventional and emerging new strategies used to manipulate glutamylation in cilia.